THE INFLUENCE OF BRAND IMAGE, ADVERTISING, AND E-SERVICE QUALITY ON SHOPEE FOOD PURCHASING DECISIONS (STUDY ON STUDENTS IN DKI JAKARTA) - Vazran Ahlan (Jurnal Manajemen, 2023)
This study aims to determine the effect of Brand Image, Advertising, and E-Service Quality on Shopee Food Purchasing Decisions (Study on Shopee food user students in Jakarta). The type of research used is quantitative research using 100 respondents processed using Smart PLS 4.0. The research results show that Brand Image has a positive and significant effect on shopee food purchasing decisions, this is evident through the tcount value of 2.279 and the significance value is 0.015. Advertising has a positive and significant impact on shopee food purchasing decisions, this is evidenced by the tcount value of 8.726 and the significance value is 0.000. E - Service Quality has a positive and significant impact on shopee food purchasing decisions, it is proven by the tcount value of 2.392 and the significance value is 0.021. Brand image, advertising, and E-Service Quality variables have a stimultan effect on Shopee Food purchasing decisions.